Madrasah, Identitas, dan Kekuasaan Kolonial: Sejarah Madrasah Nahdlatul Wathan di Semarang, 1900–1940 - Tedi Kholiludin (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2025)
This article examines the growth of the Nahdlatul Wathon Madrasah in Semarang during the colonial era. Madrasah Nahdlatul Wathon was established more than a decade before the founding of Nahdlatul Ulama (NU). As an educational institution managed by traditionalist Muslim circles, the madrasah served as a new space to embody long-standing religious values. It was a branch of a similarly named madrasah in Surabaya. This study seeks to answer three key questions: What were the background factors behind the emergence of the Nahdlatul Wathon Madrasah in Semarang? How can its emergence be understood as a social process? And how does the madrasah represent the construction of indigenous Muslim identity? Data were collected through newspapers, archival sources, and other literature that describe the colonial context. Using a socio-historical approach, this study addresses the questions above. The findings suggest that the establishment of the Nahdlatul Wathon Madra sah in Semarang was driven by the expansion of this educational institution into various cities and supported by Semarang’s ongoing modernization. Regarding social process, the madrasah in Semarang reflects a case of cultural transposition—a vessel that preserves its original meanings and values despite being situated in a different context. Ultimately, the Nahdlatul Wathon Madrasah served a dual function for the Semarang community: it provided a new space for consolidating traditional Muslim identity and offered a new articulation of Islamic identity in an urban area that was still evolving and seeking its own form.